Analysis of Fracture Midshaft Clavicle Treated by Intramedullary Device Versus Conservative - Swapnil Date; Kiran Saoji; Kushal Surana (International Journal of Research in Pharmaceutical Sciences, 2021)
Clavicle fractures account for about 2.6 to 4 % of all fractures. The best method to treat the displaced midshaft fracture of the clavicle remains a topic of debate. Although there is a large number of studies published about this topic, it is still relatively unknown as to which modality provides better long term functional outcomes and low complications rates. In our study, we have analyzed midshaft clavicle fracture treated with intramedullary device versus conservatively in terms of clinical, functional and radiological outcomes. The mean age of the patients in our study was 35.766 years. Male: Female ratio was 5.0:1.0. The mean time interval between injury and intervention was 2.1 days. Out of 30 patients, 11 patients (36.666%) had left sided fractures, while 19 patients (63.333%) had right sided fractures. Out of 30 patients, 12 patients (40%) had type 2B1 fracture according to Robinson's classification, followed by type 11 patients (36.666%) type 2B2, 6 patients (20%) type 2A1 and 1 patient (3.333%) type 2A2 fracture. Inoperative group, the mean Constant and Murley score before the intervention, at 1 month follow up, 3 months follow up and at 6 months follow up were 47.46, 76.73, 82.8 and 90.73, while in a conservative group, it was 47.53, 71.66, 79.2 and 89.46 respectively. Inoperative group, the mean Q-DASH score before the intervention, at 1 month follow up, 3 months follow up and at 6 months follow up were 29.33, 19.33, 16.86 and 13.8, while in a conservative group, it was 31.266, 22.533, 18.8 and 15.66 respectively. The final outcome, on the basis of the final Constant and Murley score in 13 patients (43.33%), was excellent, 11 patients (36.66%) was good and 6 patients (20%) was fair. Inoperative group, complications were seen in 6 patients (40%), while in the conservative group, complications were seen in 10 patients (66.66%). Thus, the functional, clinical and radiological outcome of the patients managed surgically with an intramedullary device was significantly better when compared with patients treated conservatively.